Polyphyllin B inhibited STAT3/NCOA4 pathway and restored gut microbiota to ameliorate lung tissue injury in cigarette smoke-induced mice - Qing Wang; Zhiyi He; Jinqi Zhu; Mengyun Hu; Liu Yang; Hongzhong Yang (BMC Biotechnology, 2024)
Abstract Objective Smoking was a major risk factor for chronic obstructive pulmonary disease (COPD). This study plan to explore the mechanism of Polyphyllin B in lung injury induced by cigarette smoke (CSE) in COPD. Methods Network pharmacology and molecular docking were applied to analyze the potential binding targets for Polyphyllin B and COPD. Commercial unfiltered CSE and LPS were used to construct BEAS-2B cell injury in vitro and COPD mouse models in vivo, respectively, which were treated with Polyphyllin B or fecal microbiota transplantation (FMT). CCK8, LDH and calcein-AM were used to detect the cell proliferation, LDH level and labile iron pool. Lung histopathology, Fe3+ deposition and mitochondrial morphology were observed by hematoxylin–eosin, Prussian blue staining and transmission electron microscope, respectively. ELISA was used to measure inflammation and oxidative stress levels in cells and lung tissues. Immunohistochemistry and immunofluorescence were applied to analyze the 4-HNE, LC3 and Ferritin expression. RT-qPCR was used to detect the expression of FcRn, pIgR, STAT3 and NCOA4. Western blot was used to detect the expression of Ferritin, p-STAT3/STAT3, NCOA4, GPX4, TLR2, TLR4 and P65 proteins. 16S rRNA gene sequencing was applied to detect the gut microbiota. Results Polyphyllin B had a good binding affinity with STAT3 protein, which as a target gene in COPD. Polyphyllin B inhibited CS-induced oxidative stress, inflammation, mitochondrial damage, and ferritinophagy in COPD mice. 16S rRNA sequencing and FMT confirmed that Akkermansia and Escherichia_Shigella might be the potential microbiota for Polyphyllin B and FMT to improve CSE and LPS-induced COPD, which were exhausted by the antibiotics in C + L and C + L + P mice. CSE and LPS induced the decrease of cell viability and the ferritin and LC3 expression, and the increase of NCOA4 and p-STAT3 expression in BEAS-2B cells, which were inhibited by Polyphyllin B. Polyphyllin B promoted ferritin and LC3II/I expression, and inhibited p-STAT3 and NCOA4 expression in CSE + LPS-induced BEAS-2B cells. Conclusion Polyphyllin B improved gut microbiota disorder and inhibited STAT3/NCOA4 pathway to ameliorate lung tissue injury in CSE and LPS-induced mice.